The Effectiveness of Hypercontent-Based Character Learning for Elementary School Children - Otto Fajarianto; Suyitno Muslim; Nurdin Ibrahim; Affero Ismail (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
This study aims to examine the effectiveness of hypercontent-based character learning for elementary school children. The method employed was research and development (R&D) adapting the Hannafin and Peck model with a quantitative approach. The product developed is a hypercontent-based electronic textbook containing audio, video, links, images, and QR codes accessible via smartphones and computers. The research subjects were 35 first-grade students at SD Negeri 2 Selakau Tua, Sambas Regency, West Kalimantan. Data were collected using pre-test and post-test instruments. Expert validation produced average scores of 3.14 (material expert), 3.02 (instructional design expert), and 2.93 (media expert). Field trial results showed a pre-test average of 73.31 rising to 83.00 on the post-test. The Paired T-test yielded p-value = 0.000 < 0.05. It is concluded that hypercontent-based character learning effectively improves integrity character education learning outcomes among first-grade elementary school students.